2008
DOI: 10.1007/s11240-008-9445-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous arginine on sugarcane (Saccharum sp.) somatic embryogenesis, free polyamines and the contents of the soluble proteins and proline

Abstract: The aim of this study was to evaluate the effect of arginine on sugarcane (Saccharum sp.) somatic embryogenesis, free polyamines and other nitrogenous compounds contents. Segments of leaves were used as explants to establish embryogenic cultures on media with 0 and 50.0 mg l -1 arginine. Somatic embryos formation and free polyamines, free proline and total soluble proteins contents were compared. Arginine significantly induced sugarcane somatic embryogenesis. Free proline and protein levels determined in embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 51 publications
3
15
2
14
Order By: Relevance
“…In Saccharum sp. it was observed that arginine enhanced total soluble proteins in embryogenic cultures during embryo differentiationmaturation (Nieves et al, 2008).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In Saccharum sp. it was observed that arginine enhanced total soluble proteins in embryogenic cultures during embryo differentiationmaturation (Nieves et al, 2008).…”
Section: Resultsmentioning
confidence: 98%
“…2009 The comprehension of biochemical processes is essential to elucidate the general mechanisms involved in somatic embryogenesis. However, the available information on cell metabolism and morphogenesis of embryogenetic systems is still limited (Nomura & Komamine, 1995). The histodifferentiation of somatic embryos is normally associated with changes in the synthesis and mobilization of proteins, carbohydrates, and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…In sugarcane tissue culture, the addition of arginine to culture media was found to significantly induce somatic embryogenesis and to promote plant regeneration (Nieves et al, 2008). Similarly, glycine, arginine, and cysteine positively affected somatic embryogenesis and subsequent plant regeneration; 0.75 mM glycine was the most effective treatment studied (Asad et al, 2009).…”
Section: Sugarcane Regeneration Systemsmentioning
confidence: 99%
“…In other study, TAYLOR et al (1992) described the induction of organogenic and embryogenic callus in 18 cultivars, as well as to obtain cell cultures in suspension. Plant regeneration from embryogenic callus obtained from immature leaves was observed by DIBAX et al (2011), NIEVES et al (2008, VICKERS et al (2005) and BLANCO et al (1997) and using MS medium (MURASHIGE & SKOOG, 1962) supplemented with 2,4 dichlorophenoxyacetic acid (2,4-D) and LIU (1993), using different combinations of 2,4-D, kinetin (KIN), benzylaminopurine (BAP) and calcium pantothenate. For in vitro plant regeneration it is necessary to carry out histological analyses to determine the route of regeneration in order to discover whether the origins of the plant are in somatic embryogenesis or organogenesis, and to determine whether or not this is a reliable technique for use in the genetic transformation of sugarcane.…”
Section: Introductionmentioning
confidence: 97%